Audio recording of an interview with LAPSSET project activist in Lokichar, Turkana South, Kenya - Kinyera, Paddy Banya (Oil Movements: the Production and Government of Petro-(im)mobilities in East Africa, 2020)
Original audio recording
Keywords: Mega Infrastructure; Lamu Port and Lamu-Southern Sudan-Ethiopia Transport Corridor; Kenya